How to reuse consumed batteries from electric vehicles - Sandberg, Rebecca; Sedén, Emelie (My University, 2019)
ABSTRACT Society is moving away from using finite resources and therefore the automotive industry faces a huge transformation. The vehicles of the future will be driven by electrical power and the use of lithium-ion batteries will increase dramatically. However, after some years of use, the lithium-ion batteries can only perform 80% of their maximum effect and that is not enough capacity in order for the batteries to be considered useful in these vehicles. The Swedish battery producer has a responsibility to recycle all batteries that are produced, but recycling batteries that still have 80% capacity left would be a waste of resources. Reusing these batteries in second-life applications would be a better alternative. However, there is a noticeable lack of knowledge of how to utilise the entire capacity of the battery and such knowledge has to be developed and spread in order to create a sustainable use of electric vehicles and their batteries. The aim of the project was to contribute to creating a market for the reuse of batteries from electric vehicles. The project has had both a system oriented approach and a user centered approach and the project has followed a design process. The final result is divided into two parts, content and call-to-action. Content includes the system needed in order for the reuse of consumed batteries to work, guidelines for which standards that should be implemented and design suggestions for how consumed batteries can be reused in second-life applications. For both the system and the guidelines, the main target groups are decision makers such as trade organizations and higher authorities. For the design suggestions, the target groups are companies and individuals that could benefit from reusing consumed batteries in their business or in their home. Call-to-action includes a short-film that describes the issues and a website that gathers all information in one place in order for the stakeholders to be able to take part of it. The main target group for the short-film is trade organizations and the target group for the website is basically everyone, since all can benefit from this information.
Keywords: electric vehicles, consumed batteries, second-life products, reuse, recycle; sustainability, circular economy